The impact of task value upon stress and workload levels of first year engineering students - Lindsay, Euan (UK Higher Education Academy Subject Centre, 2010)
Engineering degrees are often perceived as arduous with the large workloads involved causing much stress for the students. Students' stress levels can be affected by a range of factors, including the nature of their workload. This paper investigates first year engineering students' reported stress and workload levels and the reported size, difficulty and learning value of the tasks they are required to perform. The analysis of the gathered data shows that both task size and task difficulty have an impact upon students' perception of stress and workload. Larger and more difficult tasks lead to an increased proportion of students who report higher stress and workload levels. Task size and task difficulty were strongly linked variables - most students who reported that their workload consisted of larger tasks also reported more difficult tasks. Task value, on the other hand, appeared to have only a small impact upon students' perception of workload, and appeared to vary independently of students' perceptions of stress. This contradicts the belief that more meaningful tasks do not cause as much stress in students.